Use of new cannulated screws for primary sternal closure in high risk patients for sternal dehiscence - Cicco, Giuseppe De; Tosi, Davide; Crisci, Roberto; Bortolami, Andrea; Aquino, Tommaso Maria; Prencipe, Aldo; Matteo, Gerardo Di; Benussi, Stefano (Journal of Thoracic Disease, 2019)
Background: Median sternotomy is still the approach of choice for heart surgery and the most common sternal closure is conventional six-wire technique. Mediastinitis is the frightening complication of the median sternotomy and occurs from 1% up to 2.4% of cases with a mortality rate which ranges from 14% up to 47%. Many methods have been suggested to reinforce the sternum with the common goal to improve sternal stability and prevent mediastinitis, but there is not consensus among cardiac surgeons on the optimal way to close the sternum. For this reason, we report our experience with a sternal device that, although not entirely new as a concept, has new technical features and plays a new role in preventing sternal dehiscence, according to the most recent findings on mechanism which leads to sternal dehiscence. Methods: We enrolled 62 high risk patients for sternal dehiscence (patients with 2 well established historical risk factors), and we closed the sternum of the patients with a new surgical option consisting of passing, in a conventional six-wire sternal closure, the last sixth steel wire (Ø 1.0 mm, n° 5) through a couple of titanium cannulated screws (Ø 5.5 mm, self-tap-ping with a length from 10 to 16 mm and 2-mm increments) inserted into the 5th or 6th couple of rib cartilages. Results: Primary chest closure with cannulated screws was performed on 48 males and 14 females. The average age of patients was 67.6 years (range, 43–88 years). The average follow-up was 12.8±16.2 months (range, 1–41 months). Chronic obstructive pulmonary disease (COPD) was the most common preoperative risk factor. The average number of risk factors was 2.4 (range, 2–4). Coronary artery bypass grafting (CABG) was the most common cardiac procedure. There were no peri-operative deaths. BMI >30 Kg/m2 and diabetes were the associated of risk factors predisposing to superficial skin dehiscence. Conclusions: In our clinical experience with high risk patients, this surgical option suggests that there is evidence of an effective stabilization of standard sternal closure and this option seems a promising technique to prevent the domino effect which starts from the xifoid bone and proceeds to the manubrium with the effect of leading to sternal instability which is the first step to mediastinitis.